KENDALA PENERAPAN SERTIFIKASI KEBERLANJUTAN OLEH PERKEBUNAN KELAPA SAWIT RAKYAT DI INDONESIA: SEBUAH TINJAUAN EMPIRIS - Limetry Liana; Hermanto Siregar; Bonar Marulitua Sinaga; Dedi Budiman Hakim (DINAMIKA PERTANIAN, 2023)
Indonesian oil palm plantations, including smallholder plantations, continue to be in the spotlight and discussed in the world market, which continues to claim that the governance of oil palm plantations in Indonesia is non-sustainable. In response to this, the implementation of palm oil sustainability certification by smallholder plantations is a form of government effort to respond to related issues while increasing the competitiveness of Indonesian palm oil. The method used in this study is an empirical study of 32 scientific articles through a literature review. The results of the study showed that there were several obstacles to the implementation of sustainability certification by smallholder oil palm plantations in Indonesia, namely: (1) low knowledge of farmers about the concept of sustainability, especially good agricultural practices; (2) low institutionalization of smallholder farmers; (3) differences in perceptions of smallholder farmers who assume sustainability certification is only for rich farmers (certification costs are expensive); and (4) no guarantee that farmers receive in implementing the principles and criteria of sustainability certification. In the future, the government needs to reformulate the rules for sustainability certification in accordance with the conditions and problems faced by smallholder farmers in Indonesia.